Efeito do tipo de metal da estrutura perovsquita nas características estruturais e na utilização como adsorvente na remoção do corante vermelho congo - Souza, Andreza Alves de (2019)
Mixed oxides perovskite structure have several applications, among which can be highlighted in adsorption and catalysis. The efficiency of the perovskite in these applications is related to its composition, structure and route of synthesis. In this work was studied the metal effect in the perovskite structure, of the type LaMO3 and La0.5Ca0.5MO3 (M = Ni or Mn), in the structural and adsorptive characteristics for dye removal. The materials were synthesized by the modified proteic method, having the collagen as a chelating agent, thermally treated at 350 ºC and calcined at 900 ºC. The materials calcined at 900 ºC were characterized by Fourier Transformed Infrared spectroscopy (FTIR), X-ray diffraction (XRD) and adsorption N2 at 77 K. The results obtained using the XRD technique indicated the formation of the perovskite phase in all calcined materials, with the presence of secondary phases in some materials. The FTIR spectra identified differences between the thermally treated and calcined materials, especially with respect to the metaloxygen (M-O) bond. The modified proteic method is efficient for obtaining materials with high surface areas when compared to the materials obtained by other synthesis methods.The materials obtained were efficient adsorbents in the removal of Congo red dye (Emáx = 94%), mainly the nickel based samples that presented larger surface areas than the manganese based materials. Besides the partial substitution of the La3+ ion by the Ca2+ ion increased significantly the adsorption capacity of the material, probably due to the formation of vacancies with doping. Kinetic studies showed that the pseudo second order model fitted better to the experimental values, with the exception of the LN9-C material, best fitted to the pseudo first order model. The studies concerning the influence of adsorbent´s mass and the influence of red Congo dye´s concentration showed expected results, allowing the investigation of the interaction of the adsorbent with the adsorbate.The perovskite structure was maintained after the adsorption assays, exhibiting high efficiency of red Congo dye removal in a second use.